Muslim women’s marriage, pregnancy, abortion and spacing of children: Evidence from the United States, Iran and Malaysia - Raja Ariffin, Raja Noriza; Abdul Talib @ Abdul Mutalib, Muzalwana; Mohd Satar, Nurulhuda; Hanafi, Hanira; Othman, Azmah; Tumin, Makmor; Zahari, Rustam Khairi (Indian Institute of Health Management Research and SAGE Publications, 2017)
Background: This study investigates the decisions on marriage, pregnancy, abortion and spacing of children among Muslim women (MW) residing in the United States, Iran and Malaysia to explore the occurrences as well as socio-demographic characteristics associated with the likelihood of making an independent decision regarding sexual and reproductive health rights.